THE GENUS PITYRANTHE Thw. (Tiliaceae). - A.J.G.H KOSTERMANS (Research Center for Biology, 1961)
1. Pityranthe Thw. is incorporated in Diplodiscus Turcz.2. A discussion on the characters of both genera is presented, together with a note, concerning priority.3. An emendated description of Diplodiscus verrucosus (Thw.) Kosterm., comb. nov. is presented.